A Great Leap Forward: Changing Landscape of Shadow Energy-Maritime Economy Off the Coast of Nigeria - Balogun, Wasiu A.; Adesanya, Olusegun Paul (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
The Atlantic coast of Nigeria, especially the Niger Delta corridor is a dynamic energy-maritime space. The region witnesses a trend in continuous evolution, propelled by the intersection of the upper world and underworld economic activities, with several individual and institutional actors at its core. The underworld end of the socio-economic spectrum on which this coastal region of Nigeria is anchored is known for its robustness and has attracted significant scholarly attention. In furtherance of scholarly interrogation of the region’s informal economy, this paper critically analyses the pervasiveness, entrenchment, and dynamics of shadow energy activities in the Niger Delta. Primarily, in a theoretical construction, the study discusses trends, patterns, and overlaps in the transition of energy-maritime shadow activities in the region. The study adopts a qualitative research method; combining primary data with a synthesis of the extant literature on the region’s shadow economy and the involvement of organised crime in the region’s energy-maritime landscape. The objective of the study flows from the fact of a great leap forward in shadow economy in the region through different social realities- grievance, greed, illegality, and organised crime. The paper develops a hybrid theory of crime; enterprise-value chain as an analytical archetype to explain the latest stage in the evolution of the underworld, shadow energy-maritime activities off the coast of Nigeria.